Beberapa Kompetensi dan Sikap Keprofesian Dosen Jurusan Pendidikan Biologi FTK UIN Raden Intan Lampung - Jatmiko, Agus (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2018)
The purpose of this study was to determine the ability of lecturers in preparing instructional strategies, compiling evaluation tools, compiling teaching materials, and lecturers' attitudes toward professionalism. This type of research uses descriptive-qualitative methods. The target of the study was the Non-Permanent Lecturers who gave lectures to the Department of Biology Education, FTK Radin Intan Lampung. The results of the study: 1) the ability of lecturers in developing learning through learning strategies has not been clearly explained the use of methods, media, and time used; 2) the ability of lecturers in developing learning through ability in compiling evaluation tools, the content of questions still oriented to the material has not been much referring to indicators of achievement; 3) the ability of lecturers in developing learning through the ability to compile teaching materials as a whole still using textbooks; 4) the ability of the lecturer to develop learning through attitudes towards the lecturer profession as a whole has been able to show the attitude of the professional lecturer.